(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Chronic liver disease (CLD) poses a significant global health challenge and has become a primary cause of mortality worldwide. The development of CLD can be attributed to various factors, such as alcohol abuse, obesity and metabolic disorders, autoimmune hepatitis, and viral hepatitis. This case series explores the clinical journey and combined Ayurvedic treatments used for patients with CLD, aiming to integrate various holistic approaches to enhance overall well-being and potentially achieve remission in CLD. Data were collected at Patanjali Wellness Center, Patanjali Yogpeeth II, Haridwar, from June 2023 to December 2023. In this period of 6 months, we had taken 4 cases of chronic liver disease from IPD. The cases that we found are in the age range of 40 to 60 years. The pre- and post-treatment data on the patient’s outcomes were studied over a period of 6 months, followed by a continuous 3-month follow-up. In this case series, a positive and effective outcome was observed through a holistic strategy. After undergoing treatment, the patient’s symptoms showed a noteworthy alleviation of CLD-related symptoms. Simultaneously, the patient’s quality of life improved. Their liver function test also showed balanced parameters. At present, they are leading a normal and fulfilling life. The collective impact of these alternative therapies played a significant role in the patient’s notable recovery from CLD. Nevertheless, further investigation and exploration are necessary to facilitate larger-scale clinical trials in this area.